2022
DOI: 10.55365/1923.x2022.20.41
|View full text |Cite
|
Sign up to set email alerts
|

State Mechanisms for Stimulating Innovative Activities

Abstract: The relevance of this study lies in the fact that innovation is now becoming a key driver of economic advancement in the developing world. This provides an opportunity to generate pro-poor growth, increase output, raise welfare levels with limited resources. Innovation, as a creative but pragmatic response to constraints of all kinds, and new technological and organisational solutions that have the ability to emerge in a specific context, is therefore important not only for economic growth but also for the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Working from home arrangements are expected to continue for many workplaces and occupations even after the pandemic. The survey conducted by Statistics Canada showed that 80% of employees would like to work at least half of their hours from home once the pandemic is over 19 . Our study reinforced that WFH is not associated with increased absenteeism and presenteeism among caregivers and patients who already have high work productivity loss 22–27 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Working from home arrangements are expected to continue for many workplaces and occupations even after the pandemic. The survey conducted by Statistics Canada showed that 80% of employees would like to work at least half of their hours from home once the pandemic is over 19 . Our study reinforced that WFH is not associated with increased absenteeism and presenteeism among caregivers and patients who already have high work productivity loss 22–27 .…”
Section: Discussionsupporting
confidence: 66%
“…Smite et al 8 reviewed 13 surveys conducted in different countries to measure the changes in perceived productivity among the software engineers during the pandemic; in four surveys, most respondents reported decreased productivity; in six surveys, most respondents reported no changes; and in three surveys, most respondents reported increased productivity. Based on the Labour Force Survey conducted by Statistics Canada, 90% of employees who usually worked outside the home before the pandemic but worked most of their hours at home during February 14 to 20, 2021, reported being at least as productive as they were in their usual workplace (58% the same and 32% more productive) 19 . Awada et al 9 found that the overall perception of productivity did not change compared with in-office productivity before the pandemic among survey respondents who were WFH in the United States.…”
mentioning
confidence: 99%